2019
DOI: 10.1021/acs.jcim.9b00585
|View full text |Cite
|
Sign up to set email alerts
|

Torsional Energy Barriers of Biaryls Could Be Predicted by Electron Richness/Deficiency of Aromatic Rings; Advancement of Molecular Mechanics toward Atom-Type Independence

Abstract: Biaryl molecules are one of the most ubiquitous pharmacophores found in natural products and pharmaceuticals. In spite of this, existing molecular mechanics force fields are unable to accurately reproduce their torsional energy profiles, except in a few well-parametrized cases. This effectively limits the ability of structure-based drug design methods to correctly identify hits involving biaryls with confidence (eg. during virtual screening, employing docking and/or molecular dynamics simulations). Continuing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…It is well-appreciated that general small molecule MM force fields often fail to accurately describe torsion energy profiles observed with higher-level quantum chemical calculations [73,74], a phenomenon driven by the significant effect substituents can have on torsion profiles via electronic effects [26,75]. To overcome this limitation, many MM force fields recommend refitting torsion potentials directly to quantum chemical calculations for individual molecules in a bespoke manner [1,27].…”
Section: Improved Torsion Energetics Appear To Drive Accuracy Improvementioning
confidence: 99%
“…It is well-appreciated that general small molecule MM force fields often fail to accurately describe torsion energy profiles observed with higher-level quantum chemical calculations [73,74], a phenomenon driven by the significant effect substituents can have on torsion profiles via electronic effects [26,75]. To overcome this limitation, many MM force fields recommend refitting torsion potentials directly to quantum chemical calculations for individual molecules in a bespoke manner [1,27].…”
Section: Improved Torsion Energetics Appear To Drive Accuracy Improvementioning
confidence: 99%
“…However, since atom types are locally defined, they do not always capture long-range effects such as conjugation. This is especially problematic for torsions since the torsion energy function (or profile) of a bond is determined by a combination of local and non-local effects such as conjugation, hyperconjugation, sterics, and electrostatics [37,38,39,40,41]. In this study, we define local atoms as those within two bonds of the central bond of a torsion, and remote atoms as any atom beyond those two bonds.…”
Section: Theory and Definitionsmentioning
confidence: 99%
“…Bond orders are correlated with bond vibrational frequencies [28, 50] and WBOs are used to predict trigger bonds in high energy-density material because they are correlated with the strength of bonds [19], a property which also directly affects the torsion potential. Wei et al [48] have shown that simple rules for electron richness of aromatic systems in biaryls are a good indication of torsion force constants (specifically for K ϕ,n in equation 1); however, this measure was only developed for biaryls and it does not take into account substituents beyond the aromatic ring directly adjacent to the bond.…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by the increased length of conjugation providing more resonance stabilization, as discussed later. The B.O.>1 observed at ϕ =90° might be a result of hyperconjugation (σ–π*/σ*–π), which can lead to slight stabilization of orthogonal conformations [47a] …”
Section: Resultsmentioning
confidence: 99%